PENGARUH REKRUTMEN DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PT. ENSEVAL PUTERA MEGATRADING - Viska Annataysa; Irwan Indriyanto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
The purpose to analyze the effect of recruitment and job placement on employee performance at PT. Enseval Putera Megatrading. This research is included in the category of causal associative research using a quantitative approach. The research population. The technique used for sampling was simple random sampling. The analytical method uses simultaneous and partially linear regression analysis. The results showed that in simultaneous or partially ways the recruitment and job placement have a positive and significant effect on employee performance at PT. Enseval Putera Megatrading